A Collaborative Data Gathering Mechanism Based on Fuzzy Decision for Wireless Sensor Networks. (17th August 2015) - Si, Wen; Shi, Hui-yuan; Liu, Pan
Abstract : In spite of the increasing demand for all kinds of sensing services and applications, there still lacks a clear understanding of collaborative techniques to design collaborative protocols for wireless sensor networks. This paper proposes collaborative data gathering mechanism based on fuzzy decision for wireless sensor networks. The proposed algorithm integrates some key parameters, for example, nodes' residual energy level, the number of neighbors, centrality degree, and distance to the sink, into fuzzy decision. Numerical and simulation results validate the proposed algorithm for the networks in finding the optimum cluster heads and realizing better performances in clusters distribution and energy efficiency improvement.